JOB DEMANDS DAN WORKPLACE WELL-BEING PADA GURU SEKOLAH LUAR BIASA NEGERI - DWI KENCANA WULAN; MAHARANY PUTRI (Journal of Research and Measurement in Psychology, 2016)
This study aims to determine the effect of job demands on workplace well-being in public special school teachers. There are 126 subjects of this study who were selected by using the purposive sampling technique. This study uses quantitative method. Data collecting technique used instruments which were adapted by researcher based on The Workplace Well-Being Index and The Job Demands-Resources Questionnaire. The hypothesis was tested using the linear aggression analysis of one predictor. The result of the data analysis showed the score of F count = 32,479 > F table = 3,94 with the score of p = 0,000 (p < 0,05). This means that there is a significant effect of job demands on workplace well-being in public special school teachers and the effect is 20,8%.